AN ANYLSIS OF COMMISSIVE SPEECH ACT IN “INSIDE OUT 2” MOVIE - Wuri Wiyantari; Yasmika Baihaqi; Refai; Aulia Hanifah Qomar (English Education Study Program, 2026)
Speech Acts are utterances spoken by people to make a statement or describe something that affects the future. Examples are promises, threats, refusals, offers, warnings. This study aims to examine the use of Commissive Speech Acts in the film